2017
DOI: 10.1016/j.foodres.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

How material, visual and verbal cues on packaging influence consumer expectations and willingness to buy: The case of crisps (potato chips) in Spain

Abstract: This paper analyses the influence that certain aspects of packaging design have on the consumer expectations of a series of sensory and non-sensory attributes and on willingness to buy for a bag of crisps in Spain. A two-part experiment was conducted in which 174 people evaluated the attributes for different stimuli using an online survey. In the first part, four stimuli were created in which two factors were varied: the packaging material and the image displayed. Interaction was identified between both factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 67 publications
5
51
0
1
Order By: Relevance
“…These studies show that consumption may be higher when the number of product units displayed on the image is higher 30 and when the image occupies a larger portion of the label. 31 In a more recent paper, Rebollar et al 32 showed that the way in which crisps are depicted in the image on the package has an effect on consumer sensory expectations, which is reflected in their willingness to buy. The depiction of ready-to-eat crisps, when compared with a composition in which a raw potato is depicted, increased expectations of salty and crunchy attributes and predisposition to buy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies show that consumption may be higher when the number of product units displayed on the image is higher 30 and when the image occupies a larger portion of the label. 31 In a more recent paper, Rebollar et al 32 showed that the way in which crisps are depicted in the image on the package has an effect on consumer sensory expectations, which is reflected in their willingness to buy. The depiction of ready-to-eat crisps, when compared with a composition in which a raw potato is depicted, increased expectations of salty and crunchy attributes and predisposition to buy.…”
Section: Introductionmentioning
confidence: 99%
“…From the designer's and producer's perspective, it is quite reasonable to question whether or not the specific image chosen to be depicted on the label will affect consumer perception during tasting, even when all the options being considered are congruent, pleasant, and have a similar symbolic meaning. In this context, the choice of one particular image may influence the expectations of the consumer, 32 but it is not clear if it may also influence consumer perception of sensory and non-sensory attributes, product liking, or the willingness to buy the product again.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that having a defined product category may have influenced the results, because it would ground the studied packaging, corroborating with the idea proposed by Silayoi and Spence (): people usually are fonder of the shapes that are already known by them, because they have been more exposed to it. Additionally, the results reported by Rebollar et al () also demonstrated that similarity between images used in an experiment and the existing ones in the market may bring to participants’ minds experiences and sensations felt when consuming those brands. Rebollar et al () indicated that there is more significant relationship between packaging colour and preference (willingness to buy) for a product than between shape and preference.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, the results reported by Rebollar et al (2017) also demonstrated that similarity between images used in an experiment and the existing ones in the market may bring to participants' minds experiences and sensations felt when consuming those brands. Rebollar et al (2012) indicated that there is more significant relationship between packaging colour and preference (willingness to buy) for a product than between shape and preference.…”
Section: Con Clus Ionsmentioning
confidence: 81%
“…Moreover, packaging can be used as a differentiation tool that marketers can use in their positioning strategies (RIBEIRO et al, 2018). Therefore, in designing food package, package's design is considered an important decision, since previous studies show that packaging decisions can profoundly affect the consumer's expectations of the product quality and their willingness to buy it (REBOLLAR et al, 2017). Packaging decisions include choosing the appropriate material since it can influence the customer's perceptions since they can create a sensory transfer between touch and flavor.…”
Section: Packaging and Labelling Strategies And Brand Imagementioning
confidence: 99%